2011
DOI: 10.1002/jtr.867
|View full text |Cite
|
Sign up to set email alerts
|

Examining How Attending Motivation and Satisfaction Affects the Loyalty for Attendees at Aboriginal Festivals

Abstract: This study examined the causal relationships between motivation, satisfaction and loyalty among attendees at aboriginal festivals. A total of 789 usable questionnaires were collected from two aboriginal festivals, Amis Ilisin and Saisiyat Pas‐taai. Data analyses were performed using SPSS 15.0 and LISREL 8.70 for Windows. The analytical results indicate that motivation directly affects satisfaction and indirectly affects loyalty, whereas satisfaction directly affects attendee loyalty at aboriginal festivals. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 62 publications
(155 reference statements)
8
78
0
5
Order By: Relevance
“…Although some similarities across the studies were found, Nicholson and Pearce (2001) concluded that the importance of motivational domains differed across various contexts. Lee and Hsu (2011) in the context of two aboriginal festivals in Taiwan factor analyzed 13 motivation statements which resulted in the following three domains of motivation: cultural experiences, leisure and psychology and self-expression. Park et al (2014) examined what motivated first-time visitors to attend a wine and food festival in Florida.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some similarities across the studies were found, Nicholson and Pearce (2001) concluded that the importance of motivational domains differed across various contexts. Lee and Hsu (2011) in the context of two aboriginal festivals in Taiwan factor analyzed 13 motivation statements which resulted in the following three domains of motivation: cultural experiences, leisure and psychology and self-expression. Park et al (2014) examined what motivated first-time visitors to attend a wine and food festival in Florida.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature on festivals and events has frequently highlighted numerous benefits brought up to local communities by hosting festivals. Festivals are regarded as accelerators of economic development of local communities (Lee and Hsu, 2011). Thematic festivals provide cost-effective platforms for promotion of start-up businesses and help raising awareness of new products and preferences for locally produced goods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the high percentage of people who would like to return to Babia Góra to experience the sunrise again backs up this hypothesis. Further, that indicates tourist loyalty towards the destination, which is directly determined by the satisfaction, and indirectly affected by tourist motivation (Lee, Hsu, 2011). Tourist loyalty can also contribute to creation of the positive word of mouth of the attraction (Lee, Hsu, 2011).…”
Section: Push and Pull Motives Of Sunrise Observersmentioning
confidence: 99%